Trinucleotide repeat instability via DNA base excision repair - Lai, Yanhao (DNA Repair (Amst), 2020)
Trinucleotide repeat (TNR) instability is the cause of over 40 human neurodegenerative diseases and certain types of cancer. TNR instability can result from DNA replication, repair, recombination, and gene transcription. Emerging evidence indicates that DNA base damage and base excision repair (BER) play an active role in regulating somatic TNR instability. These processes may potentially modulate the onset and progression of TNR-related diseases, given that TNRs are hotspots of DNA base damage that are present in mammalian cells with a high frequency. In this review, we discuss the recent advances in our understanding of the molecular mechanisms underlying BER-mediated TNR instability. We initially discuss the roles of the BER pathway and locations of DNA base lesions in TNRs and their interplay with non-B form DNA structures in governing repeat instability. We then discuss how the coordinated activities of BER enzymes can modulate a balance between the removal and addition of TNRs to regulate somatic TNR instability. We further discuss how this balance can be disrupted by the crosstalk between BER and DNA mismatch repair (MMR) machinery resulting in TNR expansion. Finally, we suggest future directions regarding BER-mediated somatic TNR instability and its association with TNR disease prevention and treatment.